A pyridine-flanked diketopyrrolopyrrole (DPP)-based donor–acceptor polymer showing high mobility in ambipolar and n-channel organic thin film transistors. Issue 6 (3rd November 2014) - Sun, Bin; Hong, Wei; Aziz, Hany; Li, Yuning
Abstract : A new donor–acceptor polymer based on pyridine-flanked diketopyrrolopyrrole shows high mobilities in both ambipolar and unipolar n-type organic thin film transistors. Abstract : The synthesis and properties of a new polymer semiconductor comprising an electron accepting pyridine-flanked DPP unit and an electron-donating thieno[3, 2- b ]thiophene unit are reported. This polymer has rather low-lying energy levels, which allows transporting both electrons and holes. High crystallinity and a shorter π–π stacking distance of 0.36 nm are achieved due to the strong intermolecular interaction, which are beneficial for charge carrier transport in organic thin film transistors (OTFTs). Well-balanced high electron and hole mobilities up to 3.36 cm 2 V −1 s −1 and 2.65 cm 2 V −1 s −1, respectively, are obtained in top-gate bottom-contact OTFT devices using gold as source and drain contacts. When the contact electrodes are modified with an ultrathin layer (∼3 nm) of polyethylenimine (PEI) to suppress hole injection, a unipolar n-type semiconductor performance with a high electron mobility of 2.38 cm 2 V −1 s −1 is realized.